Analisis Perkembangan Bahasa Semantik Dan Sintaksis Anak Dalam Kegiatan Belajar Dari Rumah - Nikmatul Azizah; Anita Candra Dewi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
Language is a very important communication tool for every human being. The older the child, the more and more vocabulary development will be. Aspects that make up language include semantics and syntax. During the COVID-19 pandemic, children's semantic and syntactic language development was not well monitored, because learning was carried out remotely or Learning From Home (BDR). Parents have difficulty accompanying children to learn from home and sometimes children are less interested in doing activities because learning is not interesting so parents do not send documentation of children's learning at home. The purpose of this study was to determine the development of children's semantic and syntactic language through Learning From Home activities. This study uses the method of observation conducted on 2 children aged 4-5 years with different sexes. Observations were made by observing the documentation of children's learning from home through storytelling strategies with videos, conversing with video calls and playing video cards with letter and word cards. Based on the observations, this strategy is effective for improving children's semantic and syntactic language skills. Keywords: language development, semantics, syntax, early childhood, BDR References Dhieni, N., & Azizah, M. (2012). Tingkat Pemahaman Guru Taman Kanak-kanak (TK) Tentang Kemampuan Berbahasa Anak Usia 4 - 6 Tahun. Jurnal Ilmiah VISI P2TK PAUD NI, 98 - 105. Dini, D. P. (2011). mengasah Kemampuan Berbahasa di Usia 4 - 6 Tahun. Hutabarat, I. (2018). pemerolehan Sintaksis Bahasa Indonesia Anak Usia Dua Tahun dan Tiga Tahun di Padang Bulan . Jurnal Darma Agung, 666-667. Imroatun, I. (2017). Media Belajar Bigbook Bagi Pengembangan Baca Nyaring Anak Usia Dini. Prosiding Seminar Nasional Pembelajaran Baca, Tulis, Dan Hitung Tingkat Permulaan Bagi Anak Usia Dini, 119–127. Isna, A. (2019). Perkembangan Bahasa Anak Usia Dini. Jurnal Al Athfal, 62-69. laila, N. A. (2013). Peran Lingkungan Terhadap Optimalisasi Perkembangan Bahasa Anak Usia Dini. Jurnal Studi Gender dan Anak, 71-80. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Nurhayati, R. (2020). Analisis SWOT Pelaksanaan Perkuliahan Daring Pada Masa Pandemi COVID-19 di STAI Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 63–72. https://doi.org/10.47200/ JNAJPM.V5I1.916 Putra, A. P. (2021). EFEKTIFITAS PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19, METODE DAN EVALUASI. Intersections, 6(1), 13–22. Robingatin, & Zakiyah, U. (2019). Pengembangan Bahasa Anak Usia Dini. Sleman Yogyakarta: AR RUZZ MEDIA. Santrock, J. W. (2017). Psikologi Pendidikan (cet ke-2). Prenada Media. Surur, A. M., & Nadhirin, A. U. (2020). Manajemen Waktu Pembelajaran Daring Di Masa Pandemi Covid-19 Pada TK Dharma Wanita 1 Baleturi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2). Suwardi, I. P., R, S., & Asri, Y. (2019). pemerolehan Bahasa Pertama Pada Anak Usia Dini. Jurnal Obsesi, 265-273. Widyaningtyas, W., Shari, D., Saleh, N. R., & Asmara, B. (2021). Menigkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Melalui Media Bahan Alam Batu Pelangi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 41–52. https://doi.org/10.32678/AS-SIBYAN.V6I1.2940 Widyorini, M. D., Sahasti, j. P., & Sumarlam. (2018). Pemerolehan Bahasa pada Anak Usia 2 - 3 Tahun Melalui Metode Bernyanyi di PAUD Nur Insani Piyaman, Wonosari Gunung Kidul. Jurnal Medan Makna.